Feasability of Introducing a Thioether Ring in Vasopressin by nisBTC Co-expression in Lactococcus lactis - Li, Qian; Montalban-Lopez, Manuel; Kuipers, Oscar P. (Frontiers in Microbiology, 2019)
Introducing one or more intramolecular thioether bridges in a peptide provides a promising approach to create more stable molecules with improved pharmacodynamic properties and especially to protect peptides against proteolytic degradation. Lanthipeptides are compounds that naturally possess thioether bonds in their structure. The model lanthipeptide, nisin, is produced by Lactococcus lactis as a core peptide fused to a leader peptide. The modification machinery responsible for nisin production, including the Ser/Thr-dehydratase NisB and the cyclase NisC, can be applied for introducing a thioether bridge into peptides fused to the nisin leader peptide, e.g. to replace a disulfide bond. Vasopressin plays a key role in water homeostasis in the human body and helps to constrict blood vessels. There are two cysteine residues in the structure of wild type vasopressin, which form a disulfide bridge in the mature peptide. Here, we direct the biosynthesis of vasopressin variants in such a way that the disulfide bridge is replaced by a thioether bridge using the nisin modification machinery NisBTC. Vasopressin mutants were fused either to the nisin leader peptide directly (Type A), after the first three rings of nisin (Type B/C) or after full nisin (Type D). The type B strategy was optimal for expression. LC-MS/MS data verified the formation of a thioether bridge, which provides proof of principle for this modification in vasopressin. This is a first step prior to the necessary increase of the production yield and further purification of these peptides to finally test their biological activity in tissue and animal models.